UPAYA MENINGKATKAN MOTORIK HALUS ANAK MELALUI KEGIATAN MERAJUT BENTUK BINATANG DENGAN TALI KUR DI KB SYAFA’ATUL ULUM MUNGGUR MANGUNHARJO NGAWI - Anita Solihatul Wahidah Wahidah; Isti Handayani Handayani (Kurikula : Jurnal Pendidikan, 2022)
ABSTRACT Early childhood education is an effort to stimulate, guide, build up, and provide learning activities that can result ina child's ability and skills. The learning activities at KB Syafa'atul Ulum have been more focused on attached activity and writing and media to improve fine motor as well as on KB Syafa'atul Ulum, so the process adopted on KB Syafa'atul ulum has not stimulated child intelligence. Fine motor skills. This is because of the teacher's lack of knowledge about activities used in the learning process in the classroom, teachers are also less creative in selecting media in the learning that causes the child's fine motor to lack stimulus and to develop properly. The problem set in motion will be discussed in the process and results of the development of the child's delicate motoric growth through the weaving of an animal with the rope in KB Syafa'atul Ulum. The study is a class action study using a qualitative descriptive approach. The data source used is the primary source of data obtained from interviews and observation and secondary data derived from relevant documentation data from the playboard of KB Syafa'atul Ulum. Among the conclusions of this study are: (1) the process of increasing motoric growth in children through the activity of knitting animal forms with ropes kur in KB Syafa’atul Ulum of the year 2021/2022. Include (a) planning teaching activities, (b) strategy for learning, (c) application of the learning strategy (d) evaluation and control. (2) the results of a subtle increase in motoric growth in children through the activity of knitting animal forms with ropes kur in KB Syafa’atul Ulum. This is confirmed by an average percentage of the process and product of children starting from pre action of 52.32%, in the first cycle of 70,94% and in the second cycle of 82.60%. So it has reached a 75.00% indicator of success, even surpassing it